Association between pregnancy-induced hypertension and post-partum infection in the Instituto Materno Infantil, Bogotá, Colombia: case control study Asociación entre hipertensión inducida por el embarazo e infección postparto en el Instituto Materno Infantil de Bogotá, Colombia: estudio de casos y controles - Pio Iván Gómez; Hernando Guillermo Gaitán (Federación Colombiana de Obstetricia y Ginecología, 2004)
Introduction. Post-partum infection is one of the main causes of maternal morbidity-mortality in developing countries. Identifying factors predisposing to infection will allow intervention for preventing them or (if they cannot be prevented) using other means for reducing their impact. Toxaemia seems to increase the risk of infection developing due to alterations in cell and humoral immunity. The present work's object is to evaluate whether patients having preeclampsia have a greater risk of presenting post-partum infection. Materials and Methods. A matched case control study was carried out. Pairing by day of birth was done. Inclusion criteria: women giving birth in the Instituto Materno Infantil aged between 15 and 45. Exclusion criteria: clinical patients having infection on being admitted, immunosuppression, second stage of delivery greater than two hours, antibiotic-therapy one week before birth, post-partum eclampsia. Sample size: 95% level of confidence, 80% power, 1:1 ratio, 8% frequency of controls' exposure, estimated OR 2. It was determined that 369 patients would be required per group. The two groups were compared by using t student test paired or Wilcoxon signed ranks test (according to normality in continuous variables) and McNemar's test for percentages. Bivariable analysis was done on stratifying by birth route. Crude and adjusted OR were estimated for controlling confounders using conditional logistical regression.Results. The risk of infection was increased in mild preeclampsia (OR 8.28, 95%CI 2.04-33.5) and severe preeclampsia (OR 9.42, 95%CI 2.10-41.3). The risk of infection was also increased in adolescents (OR 3.87, 95%CI 1.75 - 8.54) and who underwent caesarean section (OR 8.17, 95%CI 2.71 - 24.62). Conclusions. Using prophylactic antibiotics must be evaluated in vaginal birth and alternatives should be evaluated in terms of duration and currently considered first-choice antibiotic schemes for prophylaxis in caesarean section in patients suffering from preeclampsia. Introducción: la infección puerperal es una de las principales causas de morbimortalidad materna en los países en desarrollo. La identificación de factores predisponentes a infección permitirá intervenirlos para prevenir su aparición o si no son prevenibles, utilizar otras medidas que disminuyan su impacto. La toxemia al parecer favorece el desarrollo de infección por alteraciones de la inmunidad celular y humoral. El objetivo del presente trabajo es evaluar si las pacientes con preeclampsia tienen mayor riesgo de presentar infección puerperal. Materiales y Métodos: se realizó un estudio de casos y controles pareados por el día del parto. Criterios de inclusión: Mujeres que tuvieron parto en el Instituto Materno Infantil, entre 15 y 45 años. Criterios de exclusión: pacientes con infección clínica al ingreso, inmunosupresión, expulsivo mayor a dos horas, antibioticoterapia una semana antes del parto, eclampsia posparto tamaño muestral: nivel de confianza del 95%, poder 80%, relación 1:1, frecuencia de exposición de los controles 8%, OR estimado: 2 se determinó se requerían 369 pacientes por grupo. Se compararon los dos grupos usando la prueba t student pareada Wilcoxon signed ranks tests, según normalidad en variables continuas y test de McNemar para proporciones. Se hizo análisis bivariado al estratificar por la vía del parto y se evaluó el OR crudo y ajustado por las variables de confusión utilizando regresión logística condicional. Resultados: el riesgo de infección estuvo aumentado en preeclampsia leve (OR 8,28 IC95% 2,04 - 33,5) y preeclampsia severa (OR 9,42 IC95% 2,10 - 41,3). En adolescentes (OR 3,87 IC95% 1,75 - 8,54) y cesáreas también se aumentó el riesgo de infección (OR 8,17 IC95% 2,71 - 24,62). Conclusiones: se deberán evaluar posibles alternativas en la duración y los esquemas antibióticos considerados de primera elección en la actualidad para la profilaxis en operación cesárea no complicada por toxemia.